2020
DOI: 10.1101/2020.09.29.318840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determination of Bacterial Surface Charge Density Via Saturation of Adsorbed Ions

Abstract: Bacterial surface charge is a critical characteristic of the cell's interfacial physiology that influences how the cell interacts with the local environment. A direct, sensitive, and accurate experimental technique capable of quantifying bacterial surface charge is needed to better understand molecular adaptations in interfacial physiology in response to environmental changes. We introduce here the method of second harmonic light scattering (SHS) which is capable of detecting the number of molecular ions adsor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, the positively charged AgNPs, especially polymer-functionalized AgNPs in the current study, generally exhibited stronger antibacterial activity than the negatively charged AgNPs over a short period of time. This is highly correlated with the electrostatic interactions between positively charged materials and the negatively charged surfaces of bacteria [41]. However, in the present study the negatively charged AgNPs undergoing polymer functionalization, such as with PVP, also exhibited similar or even better antibacterial activity.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, the positively charged AgNPs, especially polymer-functionalized AgNPs in the current study, generally exhibited stronger antibacterial activity than the negatively charged AgNPs over a short period of time. This is highly correlated with the electrostatic interactions between positively charged materials and the negatively charged surfaces of bacteria [41]. However, in the present study the negatively charged AgNPs undergoing polymer functionalization, such as with PVP, also exhibited similar or even better antibacterial activity.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, the positively charged AgNPs, especially the polymer-functionalized AgNPs in the present study, generally exhibited stronger antibacterial activity than the negatively charged AgNPs over a short period of time. This is highly correlated with the electrostatic interactions between the positively charged materials and the negatively charged surfaces of bacteria ( Wilhelm et al, 2020 ). However, in the present study the negatively charged AgNPs after polymer functionalization, such as with PVP, also exhibited similar or even better antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Previous studies have demonstrated SHS and SHG can be used to quantify molecule-membrane interactions within model systems, [31][32][33][34][35][36][37][38][39][40] eukaryotic species, 16,[41][42][43][44] and bacterial cells. 24,25,[45][46][47][48][49][50][51][52][53][54][55][56] Specifically, we have implemented this technique to elucidate how structural moieties of small molecules facilitate its transport through the Gram-positive membranes of living S. aureus and Bacillus subtilis. 47 After employing the steady-state fluorescent assays, generalized polarization (GP) of laurdan and anisotropy of diphenylhexatriene (DPH), to determine the impact of MLT on global fluidity of S. aureus membranes, we monitor the trSHS of small molecules (malachite green, 25,48,49,[57][58][59] FM 2-10, 46,47 FM 1-43, 47 and 4-Di-2-ASP 47 ) with previously documented transport behavior to assess the impact of MLT.…”
Section: Introductionmentioning
confidence: 99%